SPECIFIC PROBLEMS OF CRIMINAL LAW REGULATION UNDER THE CONDITIONS OF MARITAL STATE IN THE CONTEXT OF RESTORATION OF LAW ORDER IN THE DEOCCUPIED TERRITORIES OF UKRAINE (Bulletin of criminological association of Ukraine, 2023)
In the conditions of martial law and repulsion of the armed aggression of the Russian Federation against Ukraine, a critically important direction is to ensure a high level of regulatory and legal support for the activities of the subjects of combating crime in strict accordance with the tasks set within the framework of the legal policy of the state in its criminological and criminal law dimensions.The legislator amended the Criminal Code of Ukraine after the introduction of the legal regime of martial law in Ukraine, to ensure the constitutional order, territorial integrity, peace, protection of fundamental human rights and freedoms, property, public order and public safety from criminally illegal encroachments by legal means. However, law enforcement practice shows some difficulties arising in connection with the application of new provisions of the law.In the publication, considering the achievements of scientists and the analysis of the practice of applying the relevant criminal law norms, several problematic issues that arise in the criminal law regulation of the relevant processes are highlighted.It is summarized that the achievement of high quality of criminal law is possible only with the application of rules, techniques and means of legislative technique of its construction, the mandatory observance of which is the basis for preventing the imbalance of the system of the entire criminal legislation of Ukraine.
Keywords: crime prevention; martial law; treason; occupation; de-occupied territories; legal regulation; criminological support